Inclusion in Higher Education: Perception of students with visual impairment (Research, Society and Development, 2021)
This research analyzed the perceptions of students with visual impairments who faced difficulties related to the architectural, technological, methodological and communicational accessibility at the Federal University of Pará. In order to achieve the objectives outlined in this study, the research was characterized as an exploratory and descriptive as to the objective, the case study as to the procedure and quantitative and qualitative research as to the approach of the problem. The study was done through field research and secondary data from documents referring to the laws, decrees and ordinances which is ruled through Special Education in the Brazilian educational system. Twenty participants answered the sociodemographic and academic questionnaire and were analyzed using descriptive statistics. The participants made a negative assessment regarding the accessibility barriers existing at the university. Some of these obstacles need to be reevaluated by the institution, which in turn, has to structure itself to face the specific educational needs of these students and offer the necessary resources to favor the access and permanence of this public in the institution. Appropriate knowledge can support the planning of affirmative actions that can favor the inclusion of these students.